Aging: when the ubiquitin–proteasome machinery collapses - Mohamed A. Eldeeb (AIMS Molecular Science, 2017)
In mammalian cells, protein degradation is an essential and dynamic process that is crucial for survival, growth, differentiation and proliferation of cells. Tellingly, the majority of intracellular proteins are degraded via the ubiquitin–proteasome system (UPS). UPS-mediated protein degradation serves qualitative and quantitative roles within the cellular proteome. For instance, UPS specifically targets misfolded, aggregated, toxic, mutant and otherwise structurally abnormal proteins for destruction and hence prevent aggregation and accumulation of toxic proteins. Furthermore, several cellular regulatory proteins, including cell cycle regulators, transcription factors, DNA replication and DNA repair proteins are selectively targeted for degradation via UPS and thus contribute to maintaining protein homeostasis (proteostasis) and proper functional proteome. Concomitantly, the deregulation of proteostasis may lead to several pathological disorders including aging-associated pathologies. Remarkably, augmenting the proteasomal activity has been linked to longevity in model organisms and protect these organisms from symptoms linked to protein homeostasis disorders. Herein I comment briefly on the recent work revealing the pivotal role of ubiquitin–proteasome-mediated protein degradation with respect to regulating aging process in model organisms.